Factores que propician la informalidad de las pymes y su incidencia en el desarrollo de estas en la provincia de Trujillo, distrito de víctor larco - Mendiburu Rojas, Angel Oswaldo (2016)
This research aimed to identify and quantify the factors that encourage informality of MYPE, and as Informality affects the development of these, trying to measure the consequences for the small Peruvian businessman. It also sought to establish whether the entrepreneur decides to belong to the informal sector for reasons of escape or for reasons of exclusion. For such purposes This research has it developed from a descriptive and explanatory perspective in the District of Victor Larco of the Province of Trujillo in the field of business informality and how this becomes a determinant of sub economic development level small business, it is delimited by a quantitative nature. Informality advances in different sectors of the Peruvian economy, a correlational model was estimated to assess the impact of informality for informal MYPE, on variables that affect sales, costs, profit margins and net income, subject a bivariate correlation coefficient. This work has a quantitative approach and a non-experimental design. The high degree of informality in the District of Victor Larco province of Trujillo by the different institutions is what motivated to develop this research has allowed us to determine what the informality of PYME should be, and how it affects the group of companies, employees and activities operating outside legal and regulatory frameworks governing economic activity, ie belong to the informal sector accounts stand apart from tax burdens and legal norms, but also means not having the protection and services the state can offer.